2019
DOI: 10.1073/pnas.1906358116
|View full text |Cite
|
Sign up to set email alerts
|

Evoked potentials as a biomarker of remyelination

Abstract: Multiple sclerosis (MS) is a common cause of neurologic disease in young adults that is primarily treated with disease-modifying therapies which target the immune and inflammatory responses. Promotion of remyelination has opened a new therapeutic avenue, but how best to determine efficacy of remyelinating drugs remains unresolved. Although prolongation and then shortening of visual evoked potential (VEP) latencies in optic neuritis in MS may identify demyelination and remyelination, this has not been directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 61 publications
4
29
1
1
Order By: Relevance
“…Moreover, compensatory mechanisms may allow patients still to function, although marked damage has already occurred ( 29 ). In contrast, EPs are closely linked to the pathophysiology of disturbed signal conduction ( 7 , 8 , 14 ), regardless of whether delayed responses are clinically symptomatic or remain subclinical. The transformation of such subclinical pathology into clinical disability is the most likely explanation for the prognostic power of multimodal EP assessment [review in ( 9 )].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, compensatory mechanisms may allow patients still to function, although marked damage has already occurred ( 29 ). In contrast, EPs are closely linked to the pathophysiology of disturbed signal conduction ( 7 , 8 , 14 ), regardless of whether delayed responses are clinically symptomatic or remain subclinical. The transformation of such subclinical pathology into clinical disability is the most likely explanation for the prognostic power of multimodal EP assessment [review in ( 9 )].…”
Section: Discussionmentioning
confidence: 99%
“…Evoked potentials yield complementary information to clinical assessment as they are closely related to demyelination and measure subclinical changes, which may transform only later into clinical disability. Animal models have not only shown close correlations between demyelination and latency delay ( 6 ), but also between the recovery of delayed latencies with remyelination, bidirectionally paralleled by clinical function ( 7 , 8 ). Several clinical studies have reported that scores from multimodal EP are predictive of disease course in relapsing and progressive multiple sclerosis (MS) [review in ( 9 )], and short-term test–retest variability is reasonably low for quantitative EP scores (qEPS) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Six-week-old female C57/BL6 mice, bred at the CIB Margarita Salas-CSIC, were induced for EAE as has been done by our research group for a decade [ 68 , 69 , 70 , 71 ]. Mice were divided into three experimental groups as follows: EAE-VP3.15 (compound-treated EAE animals; n = 10), EAE-Vehicle (non-treated EAE animals; abbreviated as EAE-Veh; n = 7) and SHAM (same procedure as EAE animals except the MOG injection; n = 13).…”
Section: Methodsmentioning
confidence: 99%
“…Other paraclinical testing may include OCBs in CSF; examination of the visual system (e.g., evoked potentials, OCT) will help to characterize demyelination and may be useful in diagnosis and prognosis. [62][63][64] These measures may help to identify patients at higher risk of early worsening who may be candidates for a more aggressive treatment planeither initiation with a higher-efficacy agent, or closer monitoring and earlier planned escalation. A patient's risk status may become more apparent in the first few years after diagnosis so vigilance is needed to identify ongoing disease activity that may necessitate a prompt change to a more effective agent.…”
Section: Treatment Initiation -Relapsing Msmentioning
confidence: 99%